2021
DOI: 10.1126/science.abf3668
|View full text |Cite
|
Sign up to set email alerts
|

Glaciohydrology of the Himalaya-Karakoram

Abstract: Understanding the response of Himalayan-Karakoram (HK) rivers to climate change is crucial for ~1 billion people who partly depend on these water resources. Policymakers tasked with the sustainable water resources management for agriculture, hydropower, drinking, sanitation, and hazards require an assessment of rivers’ current status and potential future changes. This review demonstrates that glacier and snow melt are important components of HK rivers, with greater hydrological importance for the Indus than Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(89 citation statements)
references
References 239 publications
0
76
0
Order By: Relevance
“…The glacier-melt component in the Himalayan water cycle buffers the river basins against drought (Pohl et al, 2017;Pritchard, 2019), but renders them susceptible to climate-change impacts (Azam et al, 2021). The ongoing changes in temperature and precipitation (Hugonnet et al, 2021) are causing Himalayan glaciers to shrink.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The glacier-melt component in the Himalayan water cycle buffers the river basins against drought (Pohl et al, 2017;Pritchard, 2019), but renders them susceptible to climate-change impacts (Azam et al, 2021). The ongoing changes in temperature and precipitation (Hugonnet et al, 2021) are causing Himalayan glaciers to shrink.…”
Section: Introductionmentioning
confidence: 99%
“…This 'peak water' is a typical characteristic of the long-term response glaciersied catchments to sustained warming (Hock et al, 2005). Due to a lack of long-term glacio-hydro-meteorological data from the region (Miller et al, 2012;Azam et al, 2021), and uncertain climate projections (Joseph et al, 2018), a satisfactory understanding of the future changes in the runoff from Himalayan catchments may still be lacking. In this context, an understanding of the climate sensitivity of runoff from these catchments may provide useful clues about the future change in catchment runoff and its variability in the high Himalaya, and may also helpful in understanding the nature of climate response of glacierised catchments in general.…”
Section: Introductionmentioning
confidence: 99%
“…Sublimation is a substantial component of the surface mass balance in the HK glaciers (Azam et al, 2021). Wagnon et al (1999) discussed that sublimation supports the existence of high-altitude glaciers because sublimation limits Fsurface for melting by counterbalancing it through high negative LE.…”
Section: Sublimation Fraction To Winter Snowfall and Its Importancementioning
confidence: 99%
“…Most glaciers in the western Himalaya and eastern Hindu Kush are losing mass in the context of climate change (Kääb et al, 2012;Yao et al, 2012;Shean et al, 2020;Brun et al, 2017;Hugonnet et al, 2021), whereas the glaciers in the eastern Karakoram and Pamir have shown unusually little changes, including unchanged, retreated, advanced and surged glaciers (Nie et al, 2021;Brun et al, 2017;Shean et al, 2020;Kääb et al, 2012;Hewitt, 2005;Bolch et al, 2017). The spatially heterogeneous distribution and changes of glaciers are primarily explained as a result of differences in the dominant precipitation-bearing atmospheric circulation patterns that include the winter westerlies the Indian summer monsoon, their changing trends and their interactions with local extreme topography (Azam et al, 2021;Nie et al, 2021;Yao et al, 2012).…”
Section: Studmentioning
confidence: 99%